2017
DOI: 10.1002/mame.201770025
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Mater. Eng. 8/2017

Abstract: Back Cover: Focus ion beam tomography reveals subsurface multiwall carbon nanotubes in electrospun fibers that have preferentially segregated to the PMMA phase in a PDMS/PMMA blend. The carbon nanotubes could not be observed in single tomograms due to their orientation. The observed contrast is attributed to electron‐induced field effects. This is reported by Eva M. Campo, Douglas Yates, Benjamin Berson, Wudmir Rojas, Allen D. Winter, Mohan Ananth, Jorge J. Santiago‐Aviles and Eugene M. Terentjev, in article n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This has enabled the assembly of hierarchical structures in simple dry post drawing, and thus produces fibers with mechanical properties comparable to nature. Investigating fiber microstructure using a combination of 2D focused ion beam/scanning electron microscopy (FIB/SEM), [ 12 ] secondary electron hyperspectral imaging (SEHI), [ 13 ] and synchrotron ptychographic X‐ray computed tomography [ 14 ] confirming a previous hypothesis of a progressive stress‐induced phase transition in silks which enables structure development through gelation, fibrillation, and consolidation. [ 15 ]…”
Section: Introductionmentioning
confidence: 72%
“…This has enabled the assembly of hierarchical structures in simple dry post drawing, and thus produces fibers with mechanical properties comparable to nature. Investigating fiber microstructure using a combination of 2D focused ion beam/scanning electron microscopy (FIB/SEM), [ 12 ] secondary electron hyperspectral imaging (SEHI), [ 13 ] and synchrotron ptychographic X‐ray computed tomography [ 14 ] confirming a previous hypothesis of a progressive stress‐induced phase transition in silks which enables structure development through gelation, fibrillation, and consolidation. [ 15 ]…”
Section: Introductionmentioning
confidence: 72%
“…Electron tomography is undoubtedly the most pertinent technique able to perform a three-dimensional analysis of polymer / CNT microstructures. Few electron tomography studies dealt with the characterization of polymer / CNT nanocomposites [9,10,11,12,13]. To our knowledge, only Natarajan et al [14] reported a quantitative analysis of the tomograms and related the evolution of several morphological parameters with the CNT volume fraction in epoxy-based nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Improved applications also need more sophisticated and efficient characterization and analysis tools for nanofibrous materials to be designed and developed. A relevant example is provided by multimodal focused ion beam imaging, which is used for tomographic reconstruction and phase‐separation analysis of blends and carbon nanotubes in electrospun composites . The polymer stretching behaviour during electrospinning is similarly important, being at the base of the stretched conformation of macromolecules along the longitudinal axis of nanofibers.…”
mentioning
confidence: 99%